Navigating a challenging path: precision disease treatment with tailored oral nano-armor-probiotics - Anmei Chen; Ying Gong; Shaoquan Wu; Ye Du; Zhijun Liu; Yuhong Jiang; Jiahong Li; Yang-Bao Miao (Journal of Nanobiotechnology)
Abstract Oral probiotics have significant potential for preventing and treating many diseases. Yet, their efficacy is often hindered by challenges related to survival and colonization within the gastrointestinal tract. Nanoparticles emerge as a transformative solution, offering robust protection and enhancing the stability and bioavailability of these probiotics. This review explores the innovative application of nanoparticle-armored engineered probiotics for precise disease treatment, specifically addressing the physiological barriers associated with oral administration. A comprehensive evaluation of various nano-armor probiotics and encapsulation methods is provided, carefully analyzing their respective merits and limitations, alongside strategies to enhance probiotic survival and achieve targeted delivery and colonization within the gastrointestinal tract. Furthermore, the review explores the potential clinical applications of nano-armored probiotics in precision therapeutics, critically addressing safety and regulatory considerations, and proposing the innovative concept of ‘probiotic intestinal colonization with nano armor’ for brain-targeted therapies. Ultimately, this review aspires to guide the advancement of nano-armored probiotic therapies, driving progress in precision medicine and paving the way for groundbreaking treatment modalities. Graphical abstract